Analysis of Product Quality, Price, Promotion, and Location Toward Purchase Decision - Rama Muqarrabin; Yuniman Zebua; Siti Lam'ah Nasution (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This study aims to analyze product quality, price, promotion, and location as well as analyze the effect of product quality, price, promotion, and location on purchasing decisions at PT. Erafone Artha Retailindo Rantauprapat as well as knowing the relationship and contribution of each factor that influences purchasing decisions at PT. Erafone Artha Retailindo Rantauprapat. The method is a quantitative method. In this study, the population is customers or consumers at PT. Erafone Artha Retailindo Rantauprapat as many as 100 respondents. The data analysis method used is simple linear regression analysis, and hypothesis testing (partial test, simultaneous test, and coefficient of determination). Based on the results of the t-test, it is known that the product quality, price, and promotion variables have a partial effect on purchasing decisions at PT. Erafone Artha Retailindo Rantauprapat. While the location variable has no significant effect on purchasing decisions. Based on the results of the f test, it is known that product quality, price, promotion, and location have a simultaneous effect on purchasing decisions at PT. Erafone Artha Retailindo Rantauprapat in terms of f count 50,181 > from f table 2.70. Based on the R-Square of 0.679, the value of the contribution of the influence of product quality, price, promotion, and location on purchasing decisions at PT. Erafone Artha Retailindo Rantauprapat that is equal to 67.9% and the remaining 32.1% is influenced by other factors outside this research.